Food Insecurity among People Living with HIV/AIDS on ART Follower at Public Hospitals of Western Ethiopia. (1st August 2020) - Oluma, Adugna; Abadiga, Muktar; Mosisa, Getu; Etafa, Werku; Fekadu, Ginenus
Abstract : Background . Food insecurity and HIV/AIDS are intertwined in a vicious cycle through nutritional, mental health, and behavioral pathways. Food insecurity is a potentially important barrier to the success of antiretroviral treatment, increased hospitalizations, and higher morbidity among HIV-infected individuals in resource-poor settings particularly in sub-Saharan Africa including Ethiopia. Therefore, the purpose of this study was to assess the prevalence of food insecurity among people living with HIV/AIDS on follow up at public hospitals of western Ethiopia. Methods . An institutional-based cross-sectional study design was conducted on a sample of 428 among people living with HIV/AIDS on follow up at public hospitals of western Ethiopia. A systematic random sampling technique was used to include all participants. Data was collected using interviewer-administered structured questionnaires. The data were entered into Epi data version 3.1 and then exported into Statistical Package for the Social Sciences window version 21 for analysis. Descriptive and inferential statistics were employed. Bivariable logistic and multivariable logistic analyses were used with AOR at CI 95% and p < 0.05 were used. Result . The finding of the study revealed that the majority of the respondents 221(53.1%) were female. The mean age of the respondents was 32.92 ± 7.304 years and 197 (47.4%) of the study participants were between 30 to 39 years' age group. The level of food insecurity among PLWHA receiving ART therapy was 68.8% which was partitioned as mild (23.32%), moderate (29.09%), and severe (16.35%) food in secured. Being single [AOR = 3.507 1.377, 8.934 ], illiterate [AOR = 5.234 1.747, 15.686 ], cigarette smoking [AOR = 3.577 2.104, 6.081 ], presence of anemia (AOR = 2.650 1.563, 4.493 ], and inadequate dietary diversity [AOR = 2.870 1.088, 7.569 ] were predictors of food insecurity. Conclusion . The prevalence of food insecurity was high. Educational status, marital status, cigarette smoking, presence of anemia, opportunistic infection, and inadequate dietary diversity were the major significant factors affecting food insecurity. We recommended a national health policy maker to integrate food and nutrition interventions as part of a package of care, treatment, and support services for people living with HIV and ART follower patients.